2019
DOI: 10.3389/fonc.2019.00775
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Biopsy in Oligometastatic Prostate Cancer—A Biologist's Point of View

Abstract: Prostate cancer (PCa) is the main cause of cancer-related mortality in males and the diagnosis, treatment, and care of these patients places a great burden on healthcare systems globally. Clinically, PCa is highly heterogeneous, ranging from indolent tumors to highly aggressive disease. In many cases treatment—generally either radiotherapy (RT) or surgery—can be curative. Several key genetic and demographic factors such as age, family history, genetic susceptibility, and race are associated with a high inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 191 publications
1
24
0
Order By: Relevance
“…5 At present, it is believed that the characteristic markers of CTC are: N-Calcium mucin (membrane protein of calcium mucin family), vimentin (a structural cytoskeletal protein), the nuclear localization of β-catenin protein and transcription factors such as SNAIL, SNAI2, TWIST, homeobox1-ZEB1, ZEB2, and TCF3. 6 CTC can be isolated by identifying epithelial markers on the cell surface. However, it has been reported that the epithelial-mesenchymal transformation mechanism can cause epithelial cells to lose polarity, resulting in loose intercellular connections and eventually become cells with the morphology and characteristics of mesenchymal cells.…”
Section: Bpkmchmentioning
confidence: 99%
“…5 At present, it is believed that the characteristic markers of CTC are: N-Calcium mucin (membrane protein of calcium mucin family), vimentin (a structural cytoskeletal protein), the nuclear localization of β-catenin protein and transcription factors such as SNAIL, SNAI2, TWIST, homeobox1-ZEB1, ZEB2, and TCF3. 6 CTC can be isolated by identifying epithelial markers on the cell surface. However, it has been reported that the epithelial-mesenchymal transformation mechanism can cause epithelial cells to lose polarity, resulting in loose intercellular connections and eventually become cells with the morphology and characteristics of mesenchymal cells.…”
Section: Bpkmchmentioning
confidence: 99%
“…As of 2020 [ 3 ], the incidence of PCa has also increased in China [ 4 , 5 ]. Several factors have been linked to the risk of PCa, including age, family history, genetic susceptibility, race, and others [ 6 ]. Generally, the symptoms of early-stage PCa are not obvious, and by the time of diagnosis, the disease has progressed to an advanced stage with the possibility of distant metastasis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, many variables influence the actual amount and composition of the extractable cfDNA, and blood liquid biopsies may remain unsuccesful in up to 50% of the samples [8].…”
Section: Introductionmentioning
confidence: 99%